Adverse effect of smoking on cross‐sectional area of small pulmonary vessel and arterial stiffness in healthy smokers without COPD. (10th April 2019) - Jo, Hwang Hee; Park, Mi Jung; Shin, Hwa Seon; Choi, Hye Young; Na, Jae Boem; Choi, Dae Seob; Choi, Ho Cheol; Lee, Sang Min; Lee, Gyeong‐Won; Lee, Seung Jun
Abstract: Introduction: Because it induces systemic inflammation, smoking is a risk factor of atherosclerosis and pulmonary hypertension. The brachial‐ankle pulse wave velocity (baPWV) and cross‐sectional area (CSA) of small pulmonary vessels can be useful markers to assess early changes of arterial stiffness and pulmonary vascular alteration in smokers. Objectives: This study aimed to explore association between the CSA of small pulmonary vessel and arterial stiffness in healthy male smokers. Methods: We enrolled 90 male non‐smokers and 90 male smokers (age: 51.5 ± 9.7 years and 52.1 ± 7.9 years, respectively). All subjects underwent chest computed tomography (CT), pulmonary function test and baPWV measurement. We evaluated the total CSAs less than 5 mm 2 using ImageJ software and divided by the total lung area (%CSA<5). We compared the association between baPWV and %CSA<5 in two groups as well as correlations among the amount of smoking, baPWV and %CSA<5. Multiple linear regression analysis using %CSA<5 as the dependent variable was also performed. Results: The mean baPWV and mean %CSA<5 were significantly different between the smokers and non‐smokers. The pack‐years was significantly correlated with %CSA<5 ( r  = −0.631, P  < 0.001) and baPWV ( r  = 0.534, P  < 0.001) in smokers. In multiple linear regression analysis, age, pack‐years, FEV1 /FVC and baPWV were associated with %CSA<5, regardless of body mass index, blood pressure and heart rate. Conclusions: There is a dose‐response relationship between cigarette smoking and the CSA of small pulmonary vessels and arterial stiffness, respectively. Arterial stiffness, age, pack‐years and mild airflow impairment are independent predictors of small pulmonary vascular destruction in smokers.